Circular Makerspaces: the founder's view. Issue 4 (3rd September 2017) - Prendeville, Sharon; Hartung, Grit; Brass, Clare; Purvis, Erica; Hall, Ashley
Abstract: Makerspaces – open access design and fabrication workshops – provide new contexts for design practice through 'distributed production'. The global community of makerspaces has evolved quickly and in turn, substantial hype is attributed to its potential for radical sustainable innovation. In this article, we explore this potential in the context of the new 'circular economy' agenda. We focus the research on the critical role of makerspace managers/founders who are recognised as gatekeepers to circular practices. The research method is action-led including expert interviews (academics and founders/managers) as well as two generative context-mapping workshops, run at selected makerspaces in collaboration with their founders/managers. We unearth everyday 'how-to' guidance to interweave circular practices within makerspaces from the outset by: fostering an enabling culture; building local connections; nurturing individual/community capacities; and stimulating practical know-how. However, while the research reveals immense opportunities to cultivate circular literacy from within makerspaces, the prospects to ask more profound questions about our economy, through makerspace practices, are found to be compromised by day-to-day concerns. The insights from this research can act as a starting point for future work in this emerging research area.